Analisis Pemasaran Budidaya Ikan Hias Air Tawar dalam Perspektif Ekonomi Islam - Sipni Sipni; Ferdinan Ferdinan; Hendro Lisa (AL-Muqayyad, 2022)
Profitable marketing for businesses must be in accordance with sharia marketing values in Islamic economic principles, honest, reliable, intelligent, communicative and courageous. Freshwater ornamental fish farming business actors have been going well. However, there are still those who do not implement marketing in accordance with sharia marketing values. The aim is to analyze the marketing of freshwater ornamental fish in an Islamic economic perspective. This type of qualitative descriptive research. The research subjects are consumers and entrepreneurs of freshwater ornamental fish cultivation, and the object of research is freshwater ornamental fish cultivation in Tembilahan Hilir Village. Non-probability sampling technique aside by means of porposive sampling and incidental sampling. Methods of collecting interview data and documentation. Data processing techniques are data reduction, data presentation, and conclusion drawing. Business actors in marketing their businesses have implemented sharia marketing values well and are in accordance with the principles in the perspective of Islamic economics. However, this has not been maximized because business actors still lack in-depth knowledge about the value of sharia marketing which results in business actors trying to run according to their knowledge well, even though it is not optimal.